Problems of Dark Green Bulrush [Scirpus atrovirens (Wild.)] Cultivation at Tala Upazila of Satkhira District: Problems of Dark Green Bulrush Cultivation - Sardar, Johora; Bappi, Emamul Hossen; Ali, Md Yasin; Islam, Md Matiul (South Asian Journal of Agriculture, 2025)
The cultivation of Dark Green Bulrush (Scirpus atrovirens [Willd.]) has emerged as a promising avenue for socioeconomic development in Tala Upazila, Satkhira District, Bangladesh. This study explores the major challenges faced by local farmers engaged in its production. Using a descriptive and diagnostic research approach, data were collected from 41 participants selected through snowball sampling. The findings revealed waterlogging (95.6%) as the most pressing issue, followed by unsuitable land (85.6%), drought and pest problems (84.4%), salinity (83.1%), and limited access to improved technologies (70%). Moderate constraints included market access, information deficiencies, and fertilizer availability. In contrast, issues related to seeds, training, transportation, and storage were considered less significant, with the lowest concern being a lack of agricultural habituation (36.3%). The study also examined how farmers’ socioeconomic traits influenced their challenges. Variables such as age, education, family size, experience, organizational participation, and media exposure had minimal or statistically insignificant impacts. However, farm size and annual household income showed notable associations. Farmers with larger landholdings faced more difficulties, likely due to greater management demands, whereas higher household incomes corresponded with fewer constraints, possibly due to better access to resources. The research highlights the urgent need for targeted policy support, affordable financing options, and access to modern agricultural technologies to promote sustainable Dark Green Bulrush cultivation. These interventions are essential to strengthen regional and national economic resilience. South Asian J. Agric. Vol. 11, No. 2, Dec., 2025: 14-27